2012
DOI: 10.1590/s0037-86822012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in the state of Maranhão, Brazil: geographical and clinical aspects

Abstract: .3% of cases proving to be important areas for study. The western region, with a prevalence of 10.8/100,000 inhabitants, has a significantly higher proportion of cases than the northern, southern, and eastern regions (p < 0.05). The occurrence was higher in men with 89.3% of cases, and the male-to-female ratio was 8.4:1. The majority of patients were older than 20 years, lived in rural areas, and had farming or soil management as main occupation (73.8%). At CREDIP, 29 cases were diagnosed, of which 26 (89.6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 7 publications
5
23
0
Order By: Relevance
“…The local Moran's index showed the existence of spatial autocorrelation and indicated that this region in Brazil had the tendency to form mycoses endemic zones randomly during the time series. These data corroborate with those of Matos et al's study, which evaluated the historical series (1997 to 2007) of the case distribution of paracoccidioidomycosis in the state of Maranhão and indicated the highest prevalence of cases (74%) in the West and Central regions of the state. The incidence of this mycosis was influenced by human activities due to settlements in deforested areas for agriculture and livestock .…”
Section: Discussionsupporting
confidence: 91%
“…The local Moran's index showed the existence of spatial autocorrelation and indicated that this region in Brazil had the tendency to form mycoses endemic zones randomly during the time series. These data corroborate with those of Matos et al's study, which evaluated the historical series (1997 to 2007) of the case distribution of paracoccidioidomycosis in the state of Maranhão and indicated the highest prevalence of cases (74%) in the West and Central regions of the state. The incidence of this mycosis was influenced by human activities due to settlements in deforested areas for agriculture and livestock .…”
Section: Discussionsupporting
confidence: 91%
“…The acute-subacute form, also called the juvenile form, is less prevalent than the chronic form, or the adult form. However, PCM prevalence was higher in the states of Pará, Maranhão, Minas Gerais, Goiás, São Paulo and Rio de Janeiro 4,7,14,20,23,37,38 , than observed in the state of Rio Grande do Sul and in neighboring countries like Argentina and Paraguay, where the disease occurs almost exclusively in adult men 10,15,18,28 .…”
Section: Discussionmentioning
confidence: 69%
“…In Brazil, the prevalence of the acute/subacute clinical form varies by state and region as well, being rare in Rio Grande do Sul 10 and more frequent in the states of Maranhão 20,38 , Pará 13 , Minas Gerais 23 , São Paulo 6 , Mato Grosso do Sul 24 , and Rio de Janeiro 37 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Of notice, also, from a clinic-epidemiologic standpoint is the situation observed at Foz do Iguaçu, in the State of Paraná (Loth et al ., 2011), where 102 cases were diagnosed in a period of 18 months. 12 Besides the high incidence of the disease in this report, it is of special notice the elevated percentage of coinfection with tuberculosis (28,4% of all cases) and HIV (4,9%) and the 14,7% rate of death among the population studied.…”
Section: Epidemiologymentioning
confidence: 99%